3·(2-x) + 2 (x+3) = 12-2x
Răspunsuri la întrebare
Răspuns de
1
6 - 3x + 2x + 6 = 12 - 2x
-x + 2x = 12 - 12
x = 0
-x + 2x = 12 - 12
x = 0
Veveritza15:
mersi frate
Răspuns de
0
3·(2-x) + 2 ·(x+3) = 12 - 2x
6 - 3x + 2x + 6 = 12 - 2x
12 - x = 12 - 2x
-x + 2x = 12 - 12
x = 0
6 - 3x + 2x + 6 = 12 - 2x
12 - x = 12 - 2x
-x + 2x = 12 - 12
x = 0
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă